Reduced Intraoperative Blood Loss and Hypothermia in Burn Surgery using Cardiopulmonary Bypass Pumps. Issue 1 (February 2023) - Persad, Amit; Mowbrey, Kevin; Tredget, Edward
Objective: Patients presenting with total body surface area (TBSA) >40% burns require significant surgical treatment. Two substantial challenges during these surgeries are limiting blood loss and maintaining core temperatures. To overcome these challenges, several techniques have been developed, ranging from the Pitkin syringe method to the pneumatic tourniquet strategy for large-volume hyperthermic insufflation. Here, we compare the pneumatic tourniquet method to a roller pump method for maintenance of intraoperative normothermia and control of bleeding.Methods: We conducted a retrospective chart review of 20 patients presenting with TBSA >40% burns, 10 of whom were treated with the rapid infusion roller pump and 10 of whom were treated with the pneumatic tourniquet technique. Patients from each group were controlled for % TBSA, presence of inhalation injury, age, and date of admission. We reviewed transfusion requirement and the intraoperative temperatures, as well as the average intraoperative drop in temperature.Results: We observed improvement in the infusion volume, operative time, intraoperative temperature drop, minimum intraoperative temperature, estimated blood loss, and amount of required transfusion.Conclusions: Our study suggests that the rapid infusion roller pump technique is capable of achieving superior intraoperative bleeding control and temperature maintenance compared to the pneumatic tourniquet technique, resulting in decreased transfusion requirement.